Extended‐release but not immediate‐release and subcutaneous methylnaltrexone antagonizes the loperamide‐induced delay of whole‐gut transit time in healthy subjects. (20th October 2015) - Kolbow, Julia; Modess, Christiane; Wegner, Danilo; Oswald, Stefan; Maritz, Martina Alice; Rey, Hélène; Weitschies, Werner; Siegmund, Werner
Abstract: Methylnaltrexone (MNTX) is approved for subcutaneous treatment (MNTX‐SC) of opioid induced constipation. MNTX in oral immediate‐release (MNTX‐IR) and extended‐release (MNTX‐ER) dosage forms may antagonize the opioid induced delay in oro‐cecal transit time (OCT) as measured by using radiolabeled lactulose. Because lactulose acts laxative by its own and efficacy of MNTX on colon transit time (CTT) was unknown, the opioid antagonistic effects MNTX‐IR and MNTX‐ER (both 500 mg) relative to MNTX‐SC (12 mg) were evaluated in 15 healthy subjects with loperamide (LOP, 3 × 4 mg, 12 hourly) induced experimental constipation using the sulfasalazine/sulfapyridine method and radio‐opaque markers to measure OCT and whole gut transit time (WGT). MNTX‐ER significantly antagonized the LOP effects in 12 of our 15 subjects who responded to LOP with prolongation of WGT by 20.6–74.1 h (OCT by 0.50–10.5 h, CTT by 18.3–73.6 h). MNTX‐SC and MNTX‐IR were without significant influence. Compared to MNTX‐SC, bioavailability of MNTX‐IR and MNTX‐ER was 1.53–5.49 % and 0.11–1.24 %, respectively. MNTX‐SC and MNTX‐IR achieved active serum levels only for ∼3–5 h. MNTX‐ER antagonized the opioid‐induced delay of CTT most likely by local effects on µ‐opioid receptors in the colon.